Influence of Leadership and Motivation on Employee Performance in Trading Company: Case of Indonesia - Angga Pratama (International Journal of Management Science and Application, 2024)
Purpose: this study specifically aims to determine the influence of leadership and motivation on employee performance in trading company. Methods: the nature of the research used is causality the study approach utilizes quantitatively. Results: the statistical results prove that the two factors above have a positive and significant influence, both simultaneously and partially. Implications the driving factor for employees is specifically related to employees' willingness to do their jobs through the provision of appropriate and fair motivation to all employees because employee motivation will affect employee performance.